Kontibusi Mahasiswa Dalam Membangun Pendidikan Untuk Generasi Penerus Bangsa Yang Bermutu, Berkarakter, Berintegritas Di Sd Negeri 101417 Batuhorpak Tapanuli Selatan - Santa Ceacilia Pardosi (Prodi Tadris Matematika-UIN Mataram, 2022)
The Teaching Campus Program is a form of training as an agent of change in the educational challenges faced in Indonesia. This program is in the form of teaching assistance to empower students to assist the learning process in elementary and junior high schools in various regions, cities, villages, provinces, one of which is SD Negeri 101417 Batuhorpak which located on Jalan Tanotombangan, Tantom Angkola District, Batuhorpak Village, North Sumatra 22774. In this Teaching Campus program, students have a responsibility to help the school as partner teachers to innovate, have quality, have integrity, have character in learning literacy, numeracy, administration and adaptation technology. The results of this program are to instill empathy and social sensitivity in students towards the problems of the lives of the people around them, hone thinking skills in collaborating across fields of knowledge and students' diverse origins in solving the problems they face. The importance of this teaching campus is to bring students to contribute for the country, especially in the field of education.